COM656: Independent study / Faculty of Communication and Media Studies - UiTM, Faculty of Communication and Media Studies (2022)
This course offers the opportunity for students to discover their understanding of the communication and media field of study. The area of study in communication and media involved will be specifically catered to each programme within the faculty. Students will engage in discussions with their supervisor to complete the assessment given. The central theme of the report will be based upon reflective and analysis of different studies in the area of communication and media. Students will be required to explore each reflective piece and analysis with the guidance of their supervisor. The whole assessment will be based upon how students propose their ideas according to the field related and portray their thoughts and ideas that encompass the whole communication and media practices with the theories learned throughout their studies. Students should maintain constant contact with their supervisor an as this assessment requires discussion and approval. One of the most important aspects is a student should read and analyze reading materials such as books, journals, research and previous studies. There may also be additional reading, research and discussion assigned by the supervisor. At the end of the semester, students will be required to submit their reflective piece and analysis of their chosen topic.